Local Wisdoms on Luang Island, Southwest Moluccas, Indonesia and Its Implementation in Learning - Kalvin Karuna; Henderika Serpara (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
Local wisdom included cultural patterns of interpretation of certain localities, pure values, and unwritten norms, which serve the social life of a community and environment to regulate. The head of the ethnic groups in the community makeup but worries that the local wisdom are in danger lost to go. This article describes the current state of local wisdom as a cultural pattern of interpretation on the Luang Island - Indonesia. In addition, the manners, customs, and traditions of the community on the island are observed and an interview with four teenagers and ahead of the community is performed. The results of the observation and the interview are then presented and analyzed. The analysis has shown the following: (a) there are several local wisdom, which the harmony of the life of the community on the Luang island and the environment build may, for example,